2005
DOI: 10.2337/diabetes.54.10.2917
|View full text |Cite
|
Sign up to set email alerts
|

Increased Fatty Acid Desaturation and Enhanced Expression of Stearoyl Coenzyme A Desaturase Protects Pancreatic β-Cells from Lipoapoptosis

Abstract: Increased availability of fatty acids causes cell death and dysfunction in ␤-cell lines, isolated islets, and animal models of diabetes. From the MIN6 ␤-cell line, we selected two subpools that are resistant to palmitate-induced apoptosis. Protection was not universal because palmitate-resistant cells remained sensitive to cytokine-and streptozotocininduced apoptosis. Palmitate oxidation and incorporation into cholesterol ester (but not triglycerides) were significantly higher in palmitate-resistant cells than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
142
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(169 citation statements)
references
References 38 publications
24
142
1
Order By: Relevance
“…In ob/ob mice, Scd1 deficiency caused the appearance of an abnormal class of pancreatic islets with reduced insulin content, suggesting that β-cell failure is responsible for the diabetic phenotype [50 •• ]. Consistent with this model, an in-vitro study using the MIN6 β-cell line found that increased expression of Scd1 protects against lipoapoptosis due to the enhanced desaturation of cytotoxic palmitate [76].…”
Section: Scd1 Deficiency: Friend or Foe For Diabetesmentioning
confidence: 52%
“…In ob/ob mice, Scd1 deficiency caused the appearance of an abnormal class of pancreatic islets with reduced insulin content, suggesting that β-cell failure is responsible for the diabetic phenotype [50 •• ]. Consistent with this model, an in-vitro study using the MIN6 β-cell line found that increased expression of Scd1 protects against lipoapoptosis due to the enhanced desaturation of cytotoxic palmitate [76].…”
Section: Scd1 Deficiency: Friend or Foe For Diabetesmentioning
confidence: 52%
“…two diets, as it has been shown that different types of SFA have different functions and different metabolic effects (27) ; and (ii) the protective effect of unsaturated fats against the deleterious effect of SFA, as suggested by the results of some in vitro studies (28,29) . The prevalence of impaired fasting glucose was lowest in the starch group (21?4 %); this value was quite comparable to those in the other clusters, but fairly smaller than the highest value (38?1 %) in the animal products group.…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen hours after attachment, cells were treated with 0.4 mmol/l palmitate coupled to 0.9% (wt/vol.) BSA and 0.74 MBq/ml [U-14 C] palmitate (1.76 TBq/mol) for 24 h. To measure [ 14 C] palmitate incorporation, lipids were extracted from the cells and analysed by TLC as described previously [9,20]. For secretion studies, cells were further incubated in palmitatefree medium for 24 h. Lipids were extracted from the cell culture medium and analysed by TLC.…”
Section: Indirect Calorimetry Oxygen Consumption (mentioning
confidence: 99%